Risk and Triggering Factors Associated with Bronchial Asthma Among School-Going Children in an Urban City of Coastal Karnataka - Kamath, Sowmini P.; Shrishakumar, Shrividya; Jain, Animesh; Ramakrishna, Anand; Baliga, Shantharam B (Journal of Nepal Paediatric Society, 2017)
Introduction: Asthma is common in childhood and is a major public health issue. The objectives of this study were to identify risk and triggering factors associated with asthma among school children. Material and Methods: A prospective cross sectional study was conducted among 6-15 years old children, over two months in two private schools at Mangalore city. Trigger factors were assessed as per asthma trigger inventory (ATI). Responses were graded from 0-5 score based on ‘never’,’ rarely’, ‘sometimes’, ‘most of the time’ and ‘always’. A predesigned questionnaire suiting the city environment was prepared and used to assess the risk and triggering factors. Analysis was done using SPSS version 16. Results: Asthma and allergic rhinitis in parents (34.1%,40.7%), smoking at home(24.2%), exclusive breast feeding absence (27.5%),early weaning(24.2%), living in a flat (37.4%) and pets at home(37.4%) were risk factors noted. As per ATI, it was found that ‘having a cold’ was the most frequently selected trigger at 94.5% (47.3% ‘sometimes’, 2.2% ‘always’), followed by ‘running’ at 79.1% (27.5% ‘sometimes’, 13.2% ‘always’), and ‘house dust’ at 69.2% (31.9% ‘sometimes’, 6.6% ‘always’). The highest mean was for infections, (2.228, SD=0.546), followed by physical exercise (2.167, SD=0.331). Animal allergens had lowest mean (1.527, SD=0.104), followed by psychological triggers at second lowest (1.579, SD=0.181). However none of the risk and trigger factors had statistical significance with asthma. Conclusion: Avoiding exposure to probable triggers and identifying risk factors would aid in planning effective strategic measures with better quality of life.